XMRV and Public Health: The Retroviral Genome Is Not a Suitable Template for Diagnostic PCR, and Its Association with Myalgic Encephalomyelitis/Chronic Fatigue Syndrome Appears Unreliable - Panelli, Simona; Lorusso, Lorenzo; Balestrieri, Alessandro; Lupo, Giuseppe; Capelli, Enrica (Frontiers in Public Health, 2017)
A few years ago, a highly significant association between the xenotropic leukemia virus-related virus (XMRV) and myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS), a complex debilitating disease of poorly understood etiology and no definite treatment, was reported in Science, raising concern for public welfare. Successively, the failure to reproduce these findings, and the suspect that the diagnostic PCR was vitiated by laboratory contaminations, led to the retraction of the paper. Notwithstanding, XMRV continued to be the subject of researches and public debates. Occasional positivity in humans was detected also recently, even if data always appeared elusive and non reproducible. Here we discuss the current status of this controversial association and propose that a major role in the unreliability of the results was played by the XMRV genomic composition in itself. To this regard, we present bioinformatic analyses that show: (i) aspecific, spurious annealings of the available primers in multiple homologous sites of the human genome; (ii) strict homologies between of whole XMRV genome and interspersed repetitive elements widespread in mammalian genomes. To further detail this scenario, we screen several human and mammalian samples by using both published and newly designed primers. The experimental data confirm that available primers are far from being selective and specific. In conclusion, the occurrence of highly conserved, repeated DNA sequences in the XMRV genome deeply undermines the reliability of diagnostic PCRs by leading to artefactual and spurious amplifications. Together with all the other evidences, this makes the association between the XMRV retrovirus and CFS totally unreliable.